2009
DOI: 10.1186/1472-6882-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Frankincense oil derived from Boswellia carteri induces tumor cell specific cytotoxicity

Abstract: Background: Originating from Africa, India, and the Middle East, frankincense oil has been important both socially and economically as an ingredient in incense and perfumes for thousands of years. Frankincense oil is prepared from aromatic hardened gum resins obtained by tapping Boswellia trees. One of the main components of frankincense oil is boswellic acid, a component known to have anti-neoplastic properties. The goal of this study was to evaluate frankincense oil for its anti-tumor activity and signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 43 publications
2
68
0
3
Order By: Relevance
“…In other studies, it was demonstrated that some transcription factors were up-regulated by Frankincense extract. This resin also activated caspase dependent apoptotic pathway, Akt and Erk1/2, and suppressed the expression of CyclinD1 in some cancer cell lines (7,25). An important feature of necrosis was shown to elicit a proinflammatory response that might recruit immune cells to the tumor site, thereby increasing the efficacy of the chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other studies, it was demonstrated that some transcription factors were up-regulated by Frankincense extract. This resin also activated caspase dependent apoptotic pathway, Akt and Erk1/2, and suppressed the expression of CyclinD1 in some cancer cell lines (7,25). An important feature of necrosis was shown to elicit a proinflammatory response that might recruit immune cells to the tumor site, thereby increasing the efficacy of the chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Different extracts from these gum-resins might possess anti-cancer properties (7). Most of the previous studies focused on essential oil or hydroalcoholic extract of this resin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boswellia serrata is a kind of deciduous tree native to arid parts of India and China, containing Boswellic acids that chemically resemble steroids 7 . In addition, the boswellic acids and their analogs such as 11-keto-b-boswellic acid, 3-O-acetyl-b-boswellic acid and 3-O-acetyl-11-keto-boswellic acid also exhibit strong anti-cancer activities against brain tumors and leukemia cells 8 . The pentacyclic triterpenic acid named Boswellic acid present in the gum resin is responsible for its anti-inflammatory property 7 .…”
Section: Introductionmentioning
confidence: 99%